Physicochemical and Bacteriological Water Analysis of Bagmati and Bishnumati River - Shah, Pradeep Kumar; Chaturwedi, Shashi Bhushan (Tribhuvan University Journal, 2019)
Water pollution, one of the serious environmental issues of the world, results from contaminants being introduced into the natural environment. This study was conducted in the Microbiology laboratory, DAV College, Dhobighat, Lalitpur, Nepal from January to May 2018 with aims to assess the physicochemical and microbiological status of river water of Kathmandu valley. All together 60 water samples were collected, 20 water samples each from different places of Bagmati river, Bishnumati river and river junction (Teku Dovan). The physicochemical parameters including pH, ammonia and iron, hardness and alkalinity were analyzed by standard methods and the microbiological parameters such as total mesophilic count and total coliform count were analyzed by pour plate technique. Among all 60 water samples tested, the temperature (12.8°C), BOD value (3.11 mg/l), iron value (0.87 mg/l) and turbidity (102.2NTU) were found to be highest in Bagmati river water samples whereas the value of TSS (755.2 mg/l), TDS (748.4 mg/l), copper (0.01 mg/l) and COD (911.5 PPM) were found to be highest in water of Bishnumati river. The heavy meals Manganese (0.29 mg/l) and Nickel (0.01 mg/l) were detected only in Bishnumati river water samples. The river junction water samples showed the exceeded value of DO (9.56 mg/l) and chloride (0.12 mg/l). All the 60 samples showed total mesophilic counts more than 300 cfu/ml and the average number of total mesophilic counts were found to be 5.21×106 cfu/ml. The average number of total coliform counts were found to be 2.1×105 cfu/ml in the water samples of Bagmati river, Bishnumati river and river junction. Most of the tested parameter of the samples had more than the standard value of water quality indicating the deterioration of river water quality and thus may affect the aquatic as well as human and animal lives.